1990
DOI: 10.1016/0035-9203(90)90111-q
|View full text |Cite
|
Sign up to set email alerts
|

Arboreal green pit vipers (genus Trimeresurus) of south-east Asia: bites by T. albolabris and T. macrops in Thailand and a review of the literature

Abstract: In Thailand 29 patients were proved to have been bitten by arboreal green pit vipers: 24 by Trimeresurus albolabris and 5 by T. macrops. They were studied in order to define the clinical effects of envenoming, to characterize the haemostatic abnormalities and assess the efficacy of Thai Red Cross antivenom. T. macrops caused only local painful swelling, neutrophil leucocytosis and thrombocytopenia. T. albolabris caused more severe envenoming with local blistering and necrosis, shock, spontaneous systemic bleed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 16 publications
6
55
1
2
Order By: Relevance
“…Snakebite injuries are not uncommon in Asia (1)(2)(3)(4). However, reports of their clinical features and management in children are scarce, even in countries known to present a high snakebite incidence (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Snakebite injuries are not uncommon in Asia (1)(2)(3)(4). However, reports of their clinical features and management in children are scarce, even in countries known to present a high snakebite incidence (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, symptoms can recur in patients bitten by vipers because of slow absorption of the venom from the wound, as seen in this patient. 3,17 In addition, this patient had severely prolonged coagulation tests while his platelet count was relatively normal. These results were compatible with the kinetic study of venom antigen of green pit viper that showed early prolongation of coagulation test but delayed thrombocytopenia.…”
Section: Discussionmentioning
confidence: 95%
“…The main feature of its venom is its high proteolytic activity which is thought to be responsible for most of the local and systemic effects observed following envenoming by this snake [20,38,39]. Some components have been isolated, identified and cloned from the venom of this species in Thailand to understand their effects [20,21,40], but the venom of this same species in China has not been extensively studied and identified, although one component (Chitribrisin, a TLE) was previously cloned in our laboratory [9].…”
Section: Discussionmentioning
confidence: 99%